DREAM and C-fos proteins expression after treatment with Malaysian Mitragyna speciosa - Ali, Sumia R. Emhemed; Mohd Moklas, Mohamad Aris; Mat Taib, Che Norma (Research Journal of Pharmaceutical, Biological and Chemical Sciences, 2014)
The herb plant Mitragyna speciosa (MS) is indigenous in swampy region of Southeast Asia and its traditionally used as a medicine for various illnesses. Recent researches suggested that MS has analgesic effect and it has sedative and stimulant effects depended on given dose. The study aimed to investigate the histopathological changes and expression of both C-fos and DREAM that could be caused by MS extract. Dawley's Sprague rats were orally given the extract at three doses (10, 30, 100 mg/kg) for three weeks and restraint for two hours in restrainer device. The histopthological effects were assessed microscopically, and the C-fos and DREAM expression were evaluated via immunoblot. For the histopathological examination there were no significant changes among (testes, and brain), but kidney showed hypereamia at 30 and 100 mg/kg of nonstress and glumerulus shrunked at 30 mg/kg of stress rats, and for liver there was only slight hymeraemia at 30 of stress and 100 mg/kg of nonstress groups. The immunoblot results for proteins expression showed that; C-fos was expressed in prefrontal (PFC) was significantly increased (p<0.05) at dose 10 mg/kg in both stressed and non-stressed, while it decreased in hippocampus at 100 mg/kg in stressed, and did not show changes in non-stressed rats. DREAM expressed deacrese in PFC at 10 mg/kg in stressed animals, while in hippocampus DREAM expression level was raised significantly at 100 mg/kg in both stressed and non-stressed groups. Thus study showed that MS does not cause histopathological changes, but c-Fos and DREAM showed different expression in targeted areas.